Latent herpes simplex virus type 1 reactivation increases the susceptibility of neurodegenerative diseases: intervention with traditional Chinese medicine - Jie Sun; Chang-Yu Yan; Jie Niu; Ming-Hai Pan; Zhuo Luo; Wen-Jun Duan; Wen Li; Yan-Ping Wu; Wan-Yang Sun; Feng Huang; Fan-Na Liu; Hai-Zhi Liu; et al. (Compuscript Ltd, 2022)
Owing to environmental and lifestyle changes in modern society, physical and mental stress is on the rise among the population in attempting to compensate for the changes. Stress, defined as a series of non-specific responses to abnormal internal and external stimuli, has long been recognized to increase susceptibility to various diseases, including neurodegenerative diseases (NDs). Herpes simplex virus type 1 (HSV-1), a neurotropic herpes virus, establishes latent infections in the trigeminal ganglia for the lifetime of the host. Upon reactivation, the latent HSV-1 enters the lytic cycle, which not only causes a substantial production of reactive oxygen species (ROS) in the neurons, but also induces glial cells to produce inflammatory mediators, eventually resulting in neuronal damage and occurrence of NDs. Remarkably, both physical and psychological stress are common stimuli leading to latent HSV-1 reactivation. Acyclovir is a classic antiviral drug for the treatment of HSV-1 infection and recurrence, but acyclovir cannot reverse neuronal damage caused by HSV-1 reactivation. Recent studies have shown that traditional Chinese medicine (TCM) has advantages in the treatment of NDs. In addition, TCM is thought to prevent latent HSV-1 reactivation and NDs, which may involve regulation of the neuro-endocrine-immune network, treatment of emotional disorders, and modulation of oxidative stress. Understanding the mechanism underlying stress-induced reactivation of latent HSV-1 and the potential consequences of NDs is needed. TCM may be a promising alternative therapy for related diseases.